Wavelet‐based collocation technique for fractional integro‐differential equation with weakly singular kernel. Issue 4 (30th March 2021) - Mouley, Jyotirmoy; Mandal, B. N.
Abstract: Fractional integro‐differential equation (FIDE) with weakly singular kernel is an important topic in mathematics and engineering dealing with mathematical modeling and simulation of numerous systems and processes. A wavelet‐based collocation technique has been developed here to obtain approximate numerical solution of a FIDE with weakly singular kernel. The present method avoids complicated integrations and elaborate numerical calculations. The multiscale error approximation associated with this method has also been explained. The efficiency of the proposed method has been demonstrated by including some illustrative examples.